PM2.5 concentration and meteorological characteristics in Dhaka, Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2020)
Air quality in Dhaka city is gradually deteriorating due to increase of pollutants in air. This study aims to assess the concentration of particulate matter (PM) with an aerodynamic diameter ≤2.5 μm (PM2.5) and its relationship with meteorological parameters in highly polluted Dhaka city. Data for PM2.5 has been collected from the Air Now Department of State (AirNow DOS) and meteorological data from Bangladesh Meteorological Department (BMD). Study observed that 31.9% of hourly Air Quality Index (AQI) category was unhealthy while the percentage of ‘Good’ was very few. The maximum monthly average concentration was found to be 192.97±89.30 μg/m3 in the month of January while minimum average concentration was 29.98±19.37 μg/m3 in July. Besides, it also found that winter season had highest PM2.5concentration among all seasons. Moreover, the annual concentration was found to be 79.94±75.55 μg/m3 in 2017 which exceeded the National Ambient Air Quality Standard (NAAQS) and World Health Organization (WHO) standard. A number of meteorological factors are affecting to this variation. It is also found that rainfall is negatively strong and significantly correlated with the concentration of PM2.5, due to ambient dust are being settle down in the lithosphere. Annual concentration of PM2.5 was 5 times higher than standard level.Bangladesh J. Sci. Ind. Res.55(2), 89-98, 2020